Chapter III: Hungary's Struggle with Agricultural Depression and Indebtedness (Quarterly Journal of Economics, 1939)
Journal Article Chapter III: Hungary's Struggle with Agricultural Depression and Indebtedness Get access The Quarterly Journal of Economics, Volume 54, Issue 1_Part_2, November 1939, Pages 86–185, https://doi.org/10.1093/qje/54.1_Part_2.86 Published: 01 November 1939